Perancangan Virtual Tour 360° Sebagai Promosi Desa Wisata Tlingsing Untuk Pelestarian Tenun Lurik - Zaidan Ramadan Ilyas; Ichsan Tri Fandy Irawan; Rizky Vian Alfarriz; Abu Bakar Afan; Muhammad Taufik Nur Rahman; Ahmad Khoirul Anwar (Universitas Negeri Padang, 2024)
The advancement of technology and promotional media has a major influence in many fields, including tourism. This study aims to implement Virtual Tour as a promotional media for Tlingsing Tourism Village, with a primary focus on preserving the local cultural heritage of lurik weaving. This study uses qualitative methods, including interviews, observations, and documentation to collect related data. The results of this study indicate that the Virtual Tour displays the preservation of the local culture of lurik weaving in Tlingsing Village, which aims to facilitate access and increase a wider audience. This Virtual Tour shows the process of making weaving and the skills of the local community, thereby increasing awareness and appreciation of lurik weaving among young people. This study concludes that the use of modern technology in cultural promotional media not only preserves traditional arts, but also introduces the appeal of Lurik which has an impact on the village’s recognition by physically attracting tourists. Keywords: Local Cultural Heritage, Virtual Tour, Weaving, Tourism Village, Promotion